2018
DOI: 10.1007/s00431-018-3270-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotherapy or transcendental meditation versus progressive muscle relaxation exercises in the treatment of children with primary headaches: a multi-centre, pragmatic, randomised clinical study

Abstract: Many children suffer from headaches. Since stress may trigger headaches, effective techniques to cope with stress are needed. We investigated the effectiveness of two mind-body techniques, transcendental meditation (TM) or hypnotherapy (HT), and compared them with progressive muscle relaxation (PMR) exercises (active control group). Children (9–18 years) suffering from primary headaches more than two times per month received either TM (N = 42), HT (N = 45) or PMR (N = 44) for 3 months. Primary outcomes were fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
21
0
2
Order By: Relevance
“…De Paolis et al (30) found PMR with interactive imagery to be an effective adjuvant pain relief technique for terminal cancer patients. Jong et al (31) used PMR as an effective tool for pain relief in children with primary headaches.…”
Section: Discussionmentioning
confidence: 99%
“…De Paolis et al (30) found PMR with interactive imagery to be an effective adjuvant pain relief technique for terminal cancer patients. Jong et al (31) used PMR as an effective tool for pain relief in children with primary headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials excluded individual unrelated interventions, such as injections and surgery, 88 injections alone, 87 physiotherapy, 16 tricyclic antidepressants, 5 or pain medication (not further specified). 59 , 102 Only one drug trial made specific allowances for medications and dosages, including some of the same class as study interventions and opioids. 35 Another trial changed the regimen from allowing nonsteroidal anti-inflammatory drugs only in the first 6 weeks to applying no restrictions thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Only 7 trials (12%) were fully industry funded, 26 , 29 , 35 , 94 , 97 , 104 , 127 44 trials (77%) had public funders, and 5 (9%) were funded by mixed sources. 50 , 59 , 67 , 83 , 85 Funding sources were not reported in one trial. 91 Most trials were conducted in the United States (35%), followed by the United Kingdom (14%), Australia (7%), and Norway (7%).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the treatment of headache can be successful with non-pharmacological techniques, i.e. transcendental meditation, hypnotherapy and progressive muscle relaxation [17]. Further methods such as clown therapy also show surprisingly good effects in children, especially in anxiety [18].…”
Section: Discussionmentioning
confidence: 99%